Tool Path Optimization and Cost Analysis for Manufacturing Process of Master Cylinder Piston of Motorcycle Brake - Susilawati, Anita; Atmadio, Nico; Siswanto, Heri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
The tool path optimization is an important issue to get a low cost of manufacture parts using the CNC (Computer Numerical Control) machines. Programming to produce an optimum tool path for CNC machines is a key performance indicator for obtaining minimized machining time and good surface quality of parts. This paper purposes to optimized the CNC tool path generation programming and analyze the cost of manufacturing process of master cylinder piston of motorcycle brake. A Computer Aided Manufacturing (CAM) software was used to simulate an optimal tool path, which finding an efficient solution to shorten the cutting tool path generation. The simulation was performed on a roughing surface process of the work piece using 3 tool path schemes: longitudinal, diametrical and surface to parallel. The each scheme employed tool-path generation based on absolute and incremental reference methods of a CNC lathe machine. An analysis of simulation tool path time for each scheme and machining cost was investigated to get optimum and economies machining process. Hence, it was compared to actual time of machining process on CNC lathe in term of the manufacturing cost machining. The optimal processing time and the most economical cost for making a master cylinder piston of motorcycle brake was a parallel to surface scheme. Therefore, an optimization of tool path generation can minimize machining lead time, which lead to lowest cost of manufacturing parts, with keep maintain product quality.